Divided but dangerous: The fragmented far-right's push for power in the EU after the 2024 elections - Max Becker; Nicolai von Ondarza (Stiftung Wissenschaft und Politik (SWP), 2024)
Far-right forces emerged strengthened following the 2024 European Parliament elections. Nonetheless, they still remain divided within the legislative body. The European Conservatives and Reformists (ECR) made moderate gains and is now joined by the Patriots for Europe (PfE) and Europe of Sovereign Nations (ESN) groups. Although the alliance of France's National Rally and Hungary's Fidesz has made the PfE the third-largest group in the Parliament, its direct influence is likely to remain limited. After all, the core interest of the PfE and its members is more focused on funding, publicity and national arenas. The biggest prize, however, is influence in the Council and European Council, where the PfE hopes to gain more direct say via national governments. This could have a lasting impact on European politics, however, it is less likely to affect members of the EP.
Keywords: 320; 2024 European Parliament elections; Council of the European Union; European Council; European Commission; European Conservatives and Reformists (ECR); Patriots for Europe (PfE); Europe of Sovereign Nations (ESN); Fidesz; Giorgia Meloni; Viktor Orbán; Marine Le Pen; Alternative for Germany (AfD)